2017
DOI: 10.1039/c7ra06413f
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic and electrical properties in Al-substitued NiZnCo ferrite prepared via the sol–gel auto-combustion method for LTCC technology

Abstract: Al-substituted NiZnCo ferrite, Ni0.4Zn0.5Co0.1AlxFe2−xO4 (0 ≤ x ≤ 0.20), were synthesized by the sol–gel auto-combustion method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The result shows a clear transformation phase from magnetic order to disorder from 300 K to 700 K. The inset shows that the composite has a Curie temperature of about 593 K. The sample T-2 shows relatively stable magnetization at low temperatures (300–400 K). A similar result has been reported by Li et al 32 for Ni 0.4 Zn 0.5 Co 0.1 Fe 2 O 4 ferrite prepared by the sol–gel method. However, in this study, the Curie temperature of the composite is higher than that reported, which may be due to different ratios of ferrite.…”
Section: Resultssupporting
confidence: 90%
“…The result shows a clear transformation phase from magnetic order to disorder from 300 K to 700 K. The inset shows that the composite has a Curie temperature of about 593 K. The sample T-2 shows relatively stable magnetization at low temperatures (300–400 K). A similar result has been reported by Li et al 32 for Ni 0.4 Zn 0.5 Co 0.1 Fe 2 O 4 ferrite prepared by the sol–gel method. However, in this study, the Curie temperature of the composite is higher than that reported, which may be due to different ratios of ferrite.…”
Section: Resultssupporting
confidence: 90%
“…For nanometric Ni-Zn ferrites, it is possible to obtain good electric properties and high performance at relatively low sintering temperature. Recently, Li et al 22 examined the dielectric properties and direct-current resistivity of Al-substituted Ni-Zn-Co ferrite nanoparticles. Also, the magnetic properties of Ni-Zn ferrite nanocrystals depend on different sizes, shapes, and synthesis methods.…”
Section: Introductionmentioning
confidence: 99%